ТӨРИЙН АЛБАН ХААГЧЫН ЁС ЗҮЙН БАЙДАЛ: АНУ ба Монгол Улс - Томас Шевори; Д.Ундрах (Politology, 2023)
Public Officials’ Ethics: The U.S. and Mongolia The paper is a preliminary comparative analysis of civil service and elected officials’ ethics and culture issues in the U.S. and Mongolia. Since this is the first such comparison that has been made of these two systems on this issue, the paper is more designed to open debate than to draw definitive conclusions. The basic premise of the paper is that there are some interesting parallels, but also important divergences, between how corruption is perceived in the U.S. and Mongolia. Corruption is an important issue in each nation, but the issues are somewhat different in each case.